An innovative winding configuration to enhance 3-phase induction motor performance - Zuriman Anthony; Refdinal Nazir; Muhammad Imran Hamid (Institute of Advanced Engineering and Science, 2026)
A three-phase induction motor is extensively employed in the industrial sector due to its robustness and cost-effectiveness. An enhancement of this motor is underway to optimize its performance. Enhancing motor performance is intricately linked to escalating motor production expenses. Consequently, an innovative strategy is essential to enhance motor performance without incurring substantial extra expenses. This study aimed to introduce a novel approach for designing 3-phase induction motor coils to enhance motor performance without significant additional expenses. This study concentrated on the design of a 3-phase induction motor coil, rated at 1 HP, 380 V, 2 A, 4 poles, and 24 slots, and arranged in a Y-connection. We fabricated the coil using a dual-layer approach, creating magnetic pole pairs on each layer. The study's results demonstrated an improvement in output power, efficiency, load torque, and rotor speed of the new motor design, specifically by 19.32%, 16.26%, 18.48%, and 0.72%, respectively. Despite a 3.05% rise in motor coil current during peak load conditions, the motor's overall performance significantly improves, enhancing its capabilities without considerable additional expenses. This study claims that the suggested way can make other 3-phase induction motors work better without costing a lot more.